US consumer behavior during a pandemic: Precautionary measures and compensatory consumption - Jane E. Workman; Seung-Hee Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study's purposes were to examine how selected demographic variables affect frequency of use of precautionary measures when shopping for clothing in retail stores; and how uncertainty avoidance/ambiguity intolerance and fashion innovativeness affect (a) precautionary measures used when shopping in retail stores during a pandemic and (b) compensatory consumption. Participants (122 US men; 209 US women aged 20 to 64) completed an online questionnaire containing demographic items plus measures of uncertainty avoidance/ambiguity intolerance, compensatory consumption, precautionary measures, and fashion innovativeness. Data analysis included reliability, factor analysis, M/ANOVA and SNK. Older adults, adults with higher education, and married adults more frequently used precautionary measures when shopping in retail stores. Men and women reported similar frequency of use. Fashion innovators and consumers with less tolerance for uncertainty/ambiguity more frequently used precautionary measures. Fashion innovators and consumers higher in uncertainty avoidance/ambiguity intolerance engaged in more compensatory consumption. Generalization of the results is limited because the data are context-specific: country (US), time period (during a pandemic), and sample. Guidelines for the general public regarding precautionary measures came from within organizations, between organizations and experts but the general public was not consulted (public open innovation) perhaps hindering compliance with precautionary measures.
Keywords: 650; ambiguity intolerance; compensatory consumption; COVID-19 pandemic; fashion innovativeness; precautionary measures; uncertainty avoidance